Credible threat [large type] - Jance, Judith A. (Jance, Judith A. Ali Reynolds mysteries., 2020)
Ali Reynolds and her team at High Noon Enterprises must race against the clock to save an archbishop as he faces mysterious death threats in the next "devilish page-turner" (People) in the New York Times bestselling series by J.A. Jance.